Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1074/jbc.m009967200
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational Processing of Bovine Chondromodulin-I

Abstract: Chondromodulin-I (ChM-I) is a small glycoprotein that is abundant in fetal cartilage. Mature chondromodulin-I is processed from a larger precursor form, presumably at a proteolytic site RERR-ELVR. The precursor, mature chondromodulin-I and two processed products, the remnant left after removal of mature chondromodulin-I and a smaller, unglycosylated form, were identified using antipeptide antisera. The products of chondromodulin-I precursor processing were seen in cultured chondrocytes, a stable long-term cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…Mature human ChM-I (120 amino acids) is also secreted from chondrocytes as a C-terminal fragment of a type II transmembrane protein (334 amino acids) after cleavage at its furin processing site (Arg-Glu-ArgArg) . No processing occurs when this precursor cleavage site is mutated to RERQ-SLVR or when the precursor cDNA is expressed in the furin-deficient CHO cell line (Azizan et al, 2001). Similarly, TeM is a putative type II transmembrane protein containing a BRICHOS domain, the functional role of which has not been fully elucidated (Sanchez-Pulido et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mature human ChM-I (120 amino acids) is also secreted from chondrocytes as a C-terminal fragment of a type II transmembrane protein (334 amino acids) after cleavage at its furin processing site (Arg-Glu-ArgArg) . No processing occurs when this precursor cleavage site is mutated to RERQ-SLVR or when the precursor cDNA is expressed in the furin-deficient CHO cell line (Azizan et al, 2001). Similarly, TeM is a putative type II transmembrane protein containing a BRICHOS domain, the functional role of which has not been fully elucidated (Sanchez-Pulido et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We isolated and purified the factor that promoted this growth inhibition, and subsequent amino acid sequencing identified it as chondromodulin-I (ChM-I) (Hiraki et al, 1991). Transfection of ChM-I precursor cDNAs into either COS7 cells or CHO cells resulted in secretion of mature ChM-I (120 amino acids) as a 25 kDa glycoprotein following processing at the furin cleavage site of the type II membrane ChM-1 precursor protein (Azizan et al, 2001;Hiraki et al, 1997;Hiraki et al, 1999). In situ hybridization and immunohistochemistry indicated that ChM-I is specifically localized in the avascular zone of cartilage during endochondral bone formation Shukunami et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…SPCs convert a number of precursors of secreted proteins including members of the TGF␀ superfamily and most neural and peptide hormones (23). In cartilage a number of protein precursors are known to be processed by SPCs including BMP-like factors, collagen ␣1(XI), and chondromodulin-I (23)(24)(25)(26). Cleavage may occur intracellularly during secretion after removal of the signal peptide as shown for GDF5 in Xenopus embryogenesis and during mouse limb formation (26).…”
Section: Discussionmentioning
confidence: 99%
“…Proteolytic cleavage of ChM-I by furin occurs at the C-terminal of the BRICHOS domain and leads to the secretion of the C-terminal cysteine-rich domain into the ECM. The remaining membrane bound part has a short half-life and can apparently not be detected in tissue samples (3). Processing of Tnmd has not been experimentally analyzed, but a putative protease recognition sequence RXXR was identified (4).…”
mentioning
confidence: 99%